Global burden and trends of occupational noise-induced hearing loss (1990–2021) and projection to 2040 - Gong, Xin; Yi, Meitao; Jiang, Cuiping; Xiong, Qiao; Xu, Bingying; Weng, Falin; Zeng, Lingna; Lu, Rumei; Chen, Zhenglong; Yan, Chuanjiang; Li, Qingqing; Zhang, Qiang (Frontiers in Public Health, 2025)
BackgroundOccupational noise is a global issue that widely affects workers’ physical health and quality of life. This study aimed to illustrate the trends and spatiotemporal patterns of occupational noise-induced hearing loss (ONIHL) burden from 1990 to 2021 and project future trends.MethodsUtilizing the Global Burden of Disease Study (GBD) 2021 data, we calculated ONIHL disability-adjusted life years (DALYs), age-standardized DALY rates (ASDRs), and summary exposure values (SEVs) by age, sex, and the Socio-demographic Index (SDI). Inequality and decomposition analyses were used to quantify health inequalities and identify the drivers of the ONIHL burden, respectively. The autoregressive integrated moving average (ARIMA) model was used to project the disease burden until 2040.ResultsIn 2021, the global burden of ONIHL remained substantial, with a total of 7,847,444.59 DALYs (95% uncertainty intervals [UI]: 5,313,648.10–10,980,789.34), indicating a 104.46% increase compared with that in 1990. The ASDR for ONIHL in 2021 was 91.12 per 100,000 individuals (95% UI: 61.98–127.20). The ASDRs and SEVs showed remarkable growth in high-middle SDI regions, especially for females. Regionally, East Asia, South Asia, Southeast Asia, and Eastern Sub-Saharan Africa experienced the greatest ONIHL burden in the world. Spearman correlation analysis revealed a significant negative correlation between the ASDR and SDI across 21 GBD regions and 204 countries and territories. ONIHL DALYs occurred mainly in middle-aged and older adults, and men consistently presented higher DALYs and ASDRs than females. The ONIHL burden was greater in lower-SDI regions, but cross-country health inequalities did not improve. Decomposition analysis revealed population growth as the main driver. By 2040, ONIHL DALYs are predicted to increase, whereas the ASDR is projected to decrease; however, the disease burden among females will rise significantly.ConclusionThe ONIHL burden is characterized by global growth, regional divergence, and widening disparities in sex trends. Targeted actions like bolstering occupational safety in lower SDI regions, adopting gender-responsive policies for female workers in high-noise industries, and prioritizing early hearing screening and long-term monitoring of noise hazards are key to tackling the burden of ONIHL worldwide.